POSITION AND RESPONSIBILITY OF THE STATE IN REGULATION OF THE RIGHT TO A HEALTHY ENVIRONMENT (CASE STUDY OF JOB CREATION ACT AND ENVIRONMENTAL LAW ENFORCEMENT) - SITUMORANG, BENNY HARRY LEKSMON; PUTRI, VIORIZZA SUCIANI; USMAN, RAMADHAN; SUYANTO, SUYANTO; TINAMBUNAN, HEZRON SABAR ROTUA (Ganec Swara, 2025)
This study seeks to examine the role and obligations of the state in overseeing the right to a healthy environment, particularly with the enforcement of Law Number 11 of 2020 on Job Creation and pertinent Constitutional Court rulings. The right to a healthy environment is enshrined in the human rights provisions of the 1945 Constitution, therefore imposing a constitutional duty on the state to maintain equilibrium between economic progress and environmental conservation. The simplification of the environmental licensing process in the Job Creation Law has sparked discussion regarding the inadequate oversight of economic activities affecting the ecology. This study employs a normative legal methodology utilizing a statutory approach, a conceptual approach, and a case law approach. Data sources are from legislation, judicial rulings, and scientific publications pertinent to environmental policy. The study’s findings indicate that the state has not effectively fulfilled its obligations in implementing environmental legislation, particularly on oversight, penalties for violations, and public engagement. The Constitutional Court ruling underscores the significance of transparency in environmental regulation; nonetheless, policy execution frequently prioritizes financial interests over sustainable environmental safeguarding